Evaluation of Health Literacy and COVID-19 Knowledge Levels of Candidate Soldiers: A Cross-sectional Study from Ankara, Turkey - ÇEVİK, Hüsna SARICA and EMİRAL, Gülsüm ÖZTÜRK and AKSUNGUR, Abide and BULUT, Yunus Emre and BAĞCI, Hamit Harun and KILIÇARSLAN, Nuran İÇÖZ and EMİRAL, Emrah (Bangladesh Journal of Medical Science, 2024)
people’s COVID-19 knowledge and HL levels are thought to be effective in managing the pandemic. This study aimed to evaluate candidate soldiers’ HL and COVID-19 knowledge levels in the Altındağ district of Ankara, Turkey. Material and Methods A questionnaire form containing socio-demographic characteristics, 16-item European HL Survey Questionnaire, and propositions about COVID-19 was applied to candidate soldiers Who were referred for COVID-19 PCR sampling to the Altindg District Health Directorate before enlistment between December 2021_April 2022. Results and Discussion The study was completed with 668 candidate soldiers, most of whom were young adults. HL level of 20.5% was inadequate. The frequency of those who had not been vaccinated against COVID-19 was 16.8%. The COVID-19 knowledge level of those vaccinated was higher (p=0.002). The propositions about COVID-19 symptoms and correct mask use were answered correctly at the highest rate in COVID-19 knowledge level questions. The COVID-19 knowledge level score was significantly higher in those with adequate HL levels, aged 25 and over, non-smokers, and who had university or higher education levels. There was a positive correlation between the COVID-19 knowledge level and HL levels (r=0.108; p<0.001). Conclusion This study reveals the determination of HL and COVID-19 knowledge levels of candidate soldiers and related factors and supports the necessity of proactive participation of individuals with immediate action plans to increase HL and COVID-19 knowledge levels in young adults. Bangladesh Journal of Medical Science Vol. 23 No. 02 April’24 Page: 377-387